2011
DOI: 10.1186/1556-276x-6-360
|View full text |Cite
|
Sign up to set email alerts
|

Conjugate heat transfer of laminar mixed convection of a nanofluid through an inclined tube with circumferentially non-uniform heating

Abstract: Laminar mixed convection of a nanofluid consisting of water and Al2O3 in an inclined tube with heating at the top half surface of a copper tube has been studied numerically. The bottom half of the tube wall is assumed to be adiabatic (presenting a tube of a solar collector). Heat conduction mechanism through the tube wall is considered. Three-dimensional governing equations with using two-phase mixture model have been solved to investigate hydrodynamic and thermal behaviours of the nanofluid over wide range of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…Considering that the Reynolds number is the ratio of inertial forces to viscosity forces, with constant volume fraction of the nanoparticles and thus constant viscosity forces, increase or decrease of the Reynolds number will increase or decrease the inertial forces. On the other hand, the Richardson number was defined as the ratio of the Grashof number to the square of Reynolds number in reference [20] and [38]. According to the reference [37], if the above ratio is (Gr/Re 2 ≪1), there will be forced convection heat transfer and we can neglect the effect of natural convection.…”
Section: Comparison Of the Axial Evolution Of Nu In A Horizontal Tubementioning
confidence: 99%
See 1 more Smart Citation
“…Considering that the Reynolds number is the ratio of inertial forces to viscosity forces, with constant volume fraction of the nanoparticles and thus constant viscosity forces, increase or decrease of the Reynolds number will increase or decrease the inertial forces. On the other hand, the Richardson number was defined as the ratio of the Grashof number to the square of Reynolds number in reference [20] and [38]. According to the reference [37], if the above ratio is (Gr/Re 2 ≪1), there will be forced convection heat transfer and we can neglect the effect of natural convection.…”
Section: Comparison Of the Axial Evolution Of Nu In A Horizontal Tubementioning
confidence: 99%
“…Cimpean and Pop [19] investigated mixed convective heat transfer of laminar flow in an inclined channel and concluded that use of nanofluids increases heat transfer. Allahyari et al [20] studied numerically mixed convective heat transfer of water/Al 2 O 3 nanofluids laminar flow with the wall non-uniform heat flux in an inclined circular tube; they concluded…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the Nano fluid is assumed to be the homogeneous fluid. In the single-phase method, fluid and particles are in the thermal and hydrodynamic equilibrium also, moving at the same velocity [36]. This method is simpler and requires less computational time in comparison with the two-phase methods.…”
Section: Governing Equationsmentioning
confidence: 99%
“…In sudden expansion flow recirculation eddy is attached on top and bottom wall in the laminar range [1]. Allahyari et al numerically investigated conjugate mixed convection heat transfer from circular inclined tube using nanofluid [29]. They found that nanoparticle volume fraction is less influencing axial velocity profile.…”
Section: Introductionmentioning
confidence: 97%